Anode composite catalyst layer, slurry thereof, preparation method and membrane electrode
By providing a platinum conductive layer and an iridium catalyst layer in the membrane electrode to optimize its structure and performance, the problem of insufficient performance of the existing membrane electrode catalyst layer is solved, and a film electrode with low contact resistance and high stability is achieved.
Patent Information
- Application Number
- CN202411270858.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The performance of the catalyst layer of the existing membrane electrodes needs to be improved, especially in terms of contact resistance and stability, which affects its performance and service life.
A platinum conductive layer is arranged between the proton exchange membrane and the gas diffusion layer of the membrane electrode, and combined with an iridium catalyst layer, the structure and performance of the catalyst layer are optimized by controlling the particle size of the platinum nanoparticles and the mass ratio of the ionomer.
The contact resistance between the iridium catalyst layer and the gas diffusion layer is significantly reduced, the stability and catalytic activity of the membrane electrode are improved, the service life is extended, and the contact resistance and stability are balanced.
Smart Images

Figure CN119121276A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of membrane electrodes for proton exchange membrane water electrolysis, and in particular to an anode composite catalyst layer and its slurry, a preparation method, and a membrane electrode. Background Art
[0002] Membrane Electrode Assembly (MEA), also known as membrane electrode, is mainly composed of proton exchange membrane (PEM), catalyst layer (CL) and gas diffusion layer (GDL). The catalyst layer is the place where the electrochemical reaction takes place, which can significantly reduce the activation energy required for the reaction, thereby accelerating the rate of the electrochemical reaction.
[0003] The catalyst layer of the membrane electrode assembly includes an anode catalyst layer and a cathode catalyst layer, wherein the anode catalyst layer can promote the oxidation reaction (HOR) of hydrogen, and the cathode catalyst layer can promote the reduction reaction (ORR) of oxygen, both of which have a great influence on the performance of the membrane electrode.
[0004] Since the performance of the current membrane electrode has yet to be improved, it is still necessary to continue to improve the catalyst layer. Summary of the invention
[0005] The purpose of the present application is to provide an anode composite catalyst layer and its slurry, a preparation method, and a membrane electrode, so that the membrane electrode has both low contact resistance and excellent stability.
[0006] To achieve the above objectives, this application provides the following technical solutions:
[0007] In a first aspect, the present application provides an anode composite catalyst layer, located between a proton exchange membrane and a gas diffusion layer of a membrane electrode, comprising: an iridium catalyst layer, having a first surface and a second surface relative to each other, wherein the first surface faces the proton exchange membrane and the second surface faces the gas diffusion layer, and the iridium catalyst layer comprises a first ionomer and an iridium catalyst dispersed in the first ionomer; a platinum conductive layer, having a third surface and a fourth surface relative to each other, wherein the third surface contacts the second surface of the iridium catalyst layer and the fourth surface faces the gas diffusion layer, and the platinum conductive layer comprises a second ionomer and platinum nanoparticles with a particle size of 10 nm to 500 nm dispersed in the second ionomer.
[0008] In some embodiments of the first aspect, the particle size of the platinum nanoparticles is 90 nm to 120 nm; the thickness of the platinum conductive layer is 0.3 μm to 1.5 μm; and the mass ratio of the platinum nanoparticles to the second ionomer is 1:(0.35 to 0.9).
[0009] In some embodiments of the first aspect, the first ionomer and the second ionomer respectively include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820.
[0010] In some embodiments of the first aspect, the iridium catalyst is IrO2, IrRuO x1 、IrO2 / TiO2、IrO2 / NbO x1 、IrO2 / Ta2O5、IrO2 / WO x1 or IrO2 / Nb2O 5-x2 At least one of the following, wherein x1 is 1-2, and x2 is 0-3.
[0011] In a second aspect, the present application provides an anode composite catalyst layer slurry, comprising: an iridium catalyst layer slurry, the iridium catalyst layer slurry comprising: an iridium catalyst, a first ionomer and a first solvent; a platinum conductive layer slurry, the platinum conductive layer slurry comprising platinum nanoparticles with a particle size of 10nm to 500nm, a second ionomer and a second solvent.
[0012] In some embodiments of the second aspect, the mass ratio of the iridium catalyst, the first ionomer and the first solvent is 1:(0.1-0.5):(5-50); the mass ratio of the platinum nanoparticles, the second ionomer and the second solvent is 1:(0.35-0.9):(10-50).
[0013] In some embodiments of the second aspect, the first ionomer and the second ionomer respectively include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820; the iridium catalyst is IrO2, IrRuO x 、IrO2 / TiO2、IrO2 / NbO x 、IrO2 / Ta2O5、IrO2 / WO x or IrO2 / Nb2O 5-x At least one of; the first solvent and the second solvent are the same or different and are selected from at least one of isopropanol, ethylene glycol, ethanol, n-propanol and water.
[0014] In a third aspect, the present application provides a method for preparing an anode composite catalyst layer, which is prepared using the above-mentioned anode composite catalyst layer slurry.
[0015] In some embodiments of the third aspect, the preparation method includes: using iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of the proton exchange membrane of the membrane electrode by coating or transfer method; using platinum conductive layer slurry and forming a platinum conductive layer on the surface of the iridium catalyst layer by coating or transfer method; or, the preparation method includes: using platinum conductive layer slurry and forming a platinum conductive layer on a transfer material by coating or transfer method; using iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of the platinum conductive layer by coating method; transferring the stacked structure of the platinum conductive layer and the iridium catalyst layer to the surface of the proton exchange membrane by transfer method, and removing the transfer material.
[0016] In a fourth aspect, the present application provides a membrane electrode, comprising a proton exchange membrane, a gas diffusion layer and the above-mentioned anode composite catalyst layer.
[0017] Compared with the prior art, the technical solution of the present application has the following beneficial effects:
[0018] The present application sets a platinum conductive layer between the iridium catalyst layer and the gas diffusion layer, which can significantly reduce the contact resistance between the iridium catalyst layer and the gas diffusion layer, and can also reduce the thermal stress of the membrane electrode, thereby improving the stability of the membrane electrode. By controlling the particle size of the platinum nanoparticles in the platinum conductive layer, the contact resistance and stability of the membrane electrode can be further balanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The following drawings describe in detail the exemplary embodiments disclosed in this application. The same reference numerals represent similar structures in several views of the drawings. Those skilled in the art will understand that these embodiments are non-limiting, exemplary embodiments, and the drawings are only used for the purpose of illustration and description, and are not intended to limit the scope of this application. Other embodiments may also accomplish the inventive intent in this application. It should be understood that the drawings are not drawn to scale. Among them:
[0020] Figure 1 This is a schematic diagram of an exploded view of a membrane electrode according to an embodiment of the present application;
[0021] Figure 2 A schematic diagram of a process for preparing an anode composite catalyst layer according to an embodiment of the present application;
[0022] Figure 3 A schematic flow chart of a method for preparing an anode composite catalyst layer according to another embodiment of the present application;
[0023] Figure 4 This is the XRD pattern of the platinum conductive layer prepared in Example 1 of the present application;
[0024] Figure 5This is a TEM image of the platinum conductive layer prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0025] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0026] refer to Figure 1 The anode composite catalyst layer 100 provided in the present application is located between the proton exchange membrane 200 and the gas diffusion layer 300 of the membrane electrode 10, and includes: an iridium catalyst layer 110 and a platinum conductive layer 120, wherein the iridium catalyst layer 110 has a first surface 111 and a second surface 112 opposite to each other, wherein the first surface 111 faces the proton exchange membrane 200, and the second surface 112 faces the gas diffusion layer 300, and the iridium catalyst layer 110 includes a first ionomer and an iridium catalyst dispersed in the first ionomer. The iridium catalyst layer 110 is used to promote the oxidation reaction of hydrogen.
[0027] The platinum conductive layer 120 has a relative third surface 121 and a fourth surface 122, wherein the third surface 121 is in contact with the second surface 112 of the iridium catalyst layer 110, and the fourth surface 122 faces the gas diffusion layer 300, and the platinum conductive layer 120 includes a second ionomer and platinum nanoparticles dispersed in the second ionomer. The platinum conductive layer 120 can significantly reduce the contact resistance between the iridium catalyst layer 110 and the gas diffusion layer 300, so that electrons can quickly flow from the iridium catalyst layer 110 to the gas diffusion layer 300, thereby improving the current density of the proton exchange membrane electrolysis water membrane electrode. At the same time, the platinum conductive layer 120 can also optimize the interface structure between the iridium catalyst layer 110 and the gas diffusion layer 300, thereby enhancing the gas diffusion effect, helping to reduce the polarization phenomenon during the anode reaction, so that more oxygen produced by the reaction can be quickly diffused into the flow field. Therefore, the introduction of the platinum conductive layer 120 can effectively improve the performance of the proton exchange membrane electrolysis water membrane electrode.
[0028] The introduction of the platinum conductive layer 120 also helps to improve the stability and durability of the proton exchange membrane electrolysis water membrane electrode. Since platinum has good corrosion resistance and chemical stability, it can not only maintain stable performance in the harsh working environment of the proton exchange membrane electrolysis water membrane electrode, but also protect the iridium catalyst layer 110 from corrosion by electrolytes or other corrosive substances, which helps to extend the service life of the anode composite catalyst layer 100. In addition, since the platinum conductive layer 120 can reduce the contact resistance, it can solve the problem of a large amount of heat accumulation due to excessive contact resistance, thereby slowing down the thermal aging process of the proton exchange membrane electrolysis water membrane electrode.
[0029] In addition to reducing the contact resistance, the platinum conductive layer 120 can also produce a synergistic catalytic effect with the iridium catalyst layer 110, so that the catalytic activity of the anode composite catalyst layer 100 is higher than that of a single catalyst layer. At the same time, the platinum conductive layer 120 covers the iridium catalyst layer 110, which can further increase the number of active sites of the catalyst. These active sites can more effectively adsorb and convert reactants, thereby increasing the catalytic reaction rate.
[0030] The particle size of the platinum nanoparticles in the platinum conductive layer 120 has a critical effect on the contact resistance and stability of the membrane electrode. If the particle size of the platinum nanoparticles is too large, it will lead to a high contact resistance, hinder the transmission of electrons, and thus reduce the performance of the proton exchange membrane electrolysis membrane electrode; and when the particle size of the platinum nanoparticles is too small, the specific surface area of the particles is high, so the surface energy is also high, making the nanoparticles prone to aggregation, sedimentation or dissolution and other unstable phenomena. The inventors of this application have found through research that when the particle size of the platinum nanoparticles is 10nm to 500nm, the contact resistance and stability of the membrane electrode can be better balanced.
[0031] In some preferred embodiments, the particle size of the platinum nanoparticles is 90nm to 120nm. More preferably, the particle size of the platinum nanoparticles is 95nm to 110nm. Most preferably, the particle size of the platinum nanoparticles is 100nm, which can optimize the contact resistance and stability of the membrane electrode.
[0032] The thickness of the platinum conductive layer 120 will also affect the contact resistance and stability of the membrane electrode. As the thickness of the platinum conductive layer 120 increases, the path of the reaction gas from the gas diffusion layer to the surface of the catalyst layer will be extended, thereby increasing the mass transfer resistance, which will cause the diffusion rate of the reaction gas in the catalyst layer to slow down, affecting the rate and efficiency of the electrochemical reaction. At the same time, the increase in the thickness of the platinum conductive layer 120 will also increase the contact resistance, reduce the current density of the battery, and increase the generation and accumulation of heat, which is not conducive to the stability and high-voltage durability of the membrane electrode. In addition, when the platinum conductive layer 120 is too thick, it will affect the transmission and distribution of water, which may cause flooding or drying inside the membrane electrode, thereby affecting the performance and life of the battery. In some preferred embodiments, the thickness of the platinum conductive layer is 1.5μm to 1.8μm. Preferably, the thickness of the platinum conductive layer is 0.50μm to 0.70μm.
[0033] The mass ratio of the platinum nanoparticles to the second ionomer affects the electrical conductivity and ionic conductivity. In some preferred embodiments, the mass ratio of the platinum nanoparticles to the second ionomer is 1:(0.35-0.9). Preferably, the mass ratio of the platinum nanoparticles to the second ionomer is 1:(0.35-0.5).
[0034] In some preferred embodiments, the first ionomer and the second ionomer both include perfluorosulfonic acid resin. Further preferably, the first ionomer and the second ionomer each include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820. More preferably, the first ionomer and the second ionomer each include Nafion D2020.
[0035] In some preferred embodiments, the iridium catalyst is IrO2, IrRuO x1 、IrO2 / TiO2、IrO2 / NbO x1 、IrO2 / Ta2O5、IrO2 / WO x1 or IrO2 / Nb2O 5-x2 At least one of the following, wherein x1 is 1-2, and x2 is 0-3.
[0036] The present application also provides an anode composite catalyst layer slurry, comprising: an iridium catalyst layer slurry and a platinum conductive layer slurry, wherein the iridium catalyst layer slurry comprises: an iridium catalyst, a first ionomer and a first solvent; the platinum conductive layer slurry comprises platinum nanoparticles with a particle size of 10nm to 500nm, a second ionomer and a second solvent.
[0037] In some preferred embodiments, the mass ratio of the iridium catalyst, the first ionomer and the first solvent is 1:(0.1-0.5):(5-50); the mass ratio of the platinum nanoparticles, the second ionomer and the second solvent is 1:(0.35-0.9):(10-50).
[0038] In some preferred embodiments, the mass ratio of the platinum nanoparticles, the second ionomer and the second solvent is 1:(0.35-0.9):(10-50). More preferably, the ratio is 1:(0.35-0.5):(10-50). More preferably, the ratio is 1:(0.35-0.5):10.
[0039] In some preferred embodiments, the first ionomer and the second ionomer both include perfluorosulfonic acid resin. Further preferably, the first ionomer and the second ionomer each include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820. More preferably, the first ionomer and the second ionomer each include Nafion D2020.
[0040] In some preferred embodiments, the iridium catalyst is IrO2, IrRuO x1 、IrO2 / TiO2、IrO2 / NbO x1 、IrO2 / Ta2O5、IrO2 / WO x1 or IrO2 / Nb2O 5-x2 At least one of the following, wherein x1 is 1-2, and x2 is 0-3.
[0041] In some preferred embodiments, the first solvent and the second solvent are the same or different and are selected from at least one of isopropanol, ethylene glycol, ethanol, n-propanol and water.
[0042] In some preferred embodiments, the solid content of the iridium catalyst layer slurry and the platinum conductive layer slurry is 6 wt % to 15 wt %.
[0043] The present application also provides a method for preparing an anode composite catalyst layer, which is prepared by using the above-mentioned anode composite catalyst layer slurry.
[0044] refer to Figure 2 In some embodiments, the method for preparing the anode composite catalyst layer comprises the following steps:
[0045] S1: using an iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of a proton exchange membrane of a membrane electrode by a coating method or a transfer method;
[0046] S2: using a platinum conductive layer slurry and forming a platinum conductive layer on the surface of the iridium catalyst layer by a coating method or a transfer method.
[0047] refer to Figure 3 In some other embodiments, the method for preparing the anode composite catalyst layer comprises the following steps:
[0048] S10: using a platinum conductive layer slurry and forming a platinum conductive layer on a transfer material by a coating method or a transfer method;
[0049] S20: using an iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of the platinum conductive layer by a coating method;
[0050] S30: transferring the stacked structure of the platinum conductive layer and the iridium catalyst layer to the surface of the proton exchange membrane by a transfer method, and removing the transfer material.
[0051] The steps of forming the film layer by the coating method and the transfer method are all carried out in a known manner.
[0052] The present application also provides a membrane electrode, comprising a proton exchange membrane, a gas diffusion layer and the above-mentioned anode composite catalyst layer. The proton exchange membrane and the gas diffusion layer can adopt any existing structure or material.
[0053] In some specific embodiments, the gas diffusion layer is a titanium porous diffusion layer.
[0054] In some specific embodiments, the proton exchange membrane is a perfluorosulfonic acid-based proton membrane.
[0055] In some specific embodiments, the membrane electrode further includes other common membrane layer structures, such as a cathode catalyst layer adjacent to the proton exchange membrane.
[0056] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solution of the present application. Unless otherwise specified, the reagents and raw materials used can be purchased through commercial channels. The experimental methods in the following examples that do not specify specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0057] Iridium oxide particles were purchased from Heraeus, model H2EL-IrO; platinum nanoparticles were purchased from Johnson Matthey, model HISPEC1000; Nafion D2020 was purchased from Chemours.
[0058] Example 1
[0059] The present embodiment provides an anode composite catalyst layer and a preparation method thereof, wherein the anode composite catalyst layer comprises an iridium catalyst layer and a platinum conductive layer, wherein the iridium catalyst layer comprises Nafion D2020 and iridium oxide particles dispersed in the Nafion D2020, and the platinum conductive layer comprises Nafion D2020 and platinum nanoparticles with a particle size of 100 nm dispersed in the Nafion D2020.
[0060] The method for preparing the anode composite catalyst layer comprises the following steps:
[0061] (1) 2 g of 100 nm platinum nanoparticles, 1 g of Nafion D2020, 15 g of isopropanol, and 5 g of deionized water were mixed to obtain a platinum conductive layer slurry; 2 g of iridium oxide particles, 1 g of Nafion D2020, 5 g of isopropanol, and 5 g of deionized water were mixed to obtain an iridium catalyst layer slurry.
[0062] (2) The platinum conductive layer slurry is coated on a PTFE substrate using a coating machine, and a platinum conductive layer of 0.50 μm to 0.70 μm is obtained after drying.
[0063] (3) Using a coating machine, the iridium catalyst layer slurry is coated on the surface of the platinum conductive layer, and then dried to obtain an iridium catalyst layer, wherein the thickness of the iridium catalyst layer is 5.0 μm to 5.3 μm.
[0064] Example 2
[0065] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this embodiment are different only in that the particle size of the platinum nanoparticles is 10 nm.
[0066] Example 3
[0067] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this embodiment are different only in that the particle size of the platinum nanoparticles is 50 nm.
[0068] Example 4
[0069] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this embodiment are different only in that the particle size of the platinum nanoparticles is 200 nm.
[0070] Example 5
[0071] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this embodiment are different only in that the particle size of the platinum nanoparticles is 500 nm.
[0072] Example 6
[0073] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this embodiment are different only in that the thickness of the platinum conductive layer is 1 μm to 1.5 μm.
[0074] Comparative Example 1
[0075] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this comparative example are different only in that the particle size of the platinum nanoparticles is 5 nm.
[0076] Comparative Example 2
[0077] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this comparative example are different only in that the particle size of the platinum nanoparticles is 550 nm.
[0078] Comparative Example 3
[0079] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this comparative example are different only in that the mass ratio of platinum nanoparticles to Nafion D2020 is 1:0.33.
[0080] Comparative Example 4
[0081] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this comparative example are different only in that the mass ratio of platinum nanoparticles to Nafion D2020 is 1:1.
[0082] Comparative Example 5
[0083] Compared with Example 1, the anode composite catalyst layer and the preparation method thereof of this comparative example are different only in that the thickness of the platinum conductive layer is 0.1 μm to 0.2 μm.
[0084] Comparative Example 6
[0085] This comparative example provides an anode catalyst layer and a preparation method thereof. The anode catalyst layer includes Nafion D2020 and iridium oxide particles dispersed in the Nafion D2020.
[0086] The method for preparing the anode catalyst layer comprises the following steps:
[0087] (1) 2 g of iridium oxide particles, 1 g of Nafion D2020, 5 g of isopropanol and 5 g of deionized water were mixed uniformly to obtain an anode catalyst layer slurry.
[0088] (2) Using a coating machine, the anode catalyst layer slurry is coated on the surface of the perfluorosulfonic acid-based sub-membrane, and then dried to obtain the anode catalyst layer.
[0089] Performance characterization:
[0090] 1) X-ray diffractometer (Rigaku D / max-2500B2+ / PC) was used to perform XRD test on the platinum conductive layer prepared in Example 1, with a scanning range of 10° to 90° and an angle increment of 0.03° / second. Please refer to the test results. Figure 4 .Depend on Figure 4 It can be seen that the crystal lattice of the sample corresponds to the standard card result of platinum, and the average particle size D of the platinum black particles calculated according to the following Sherrer equation is 102 nm.
[0091] D = Kλ / (βcosθ);
[0092] In the above formula, K is a constant; λ is the wavelength of X-rays; β is the half-height width of the diffraction peak; θ is the diffraction angle. The value of the constant K in the above formula is related to the definition of β. When β is the half-width height, K is 0.89; when β is the integral width, K is 1.0.
[0093] 2) The platinum conductive layer prepared in Example 1 was tested by TEM using a FEI TECNAI G2 F20 200KV field emission transmission electron microscope, with an acceleration voltage of 200KV. The test results are shown in Figure 5 .exist Figure 5 In the figure, the film layer in the red box is the platinum conductive layer, and the film layer between the red arrows is the iridium catalyst layer. The thickness of the platinum conductive layer is 0.50-0.70 μm, and the dispersion between the platinum nanoparticles is good without agglomeration.
[0094] Contact resistance test: Conduct contact resistance test in accordance with standard GB / T 20042.6-2011.
[0095] Stability test:
[0096] The laminated structure of the platinum conductive layer and the iridium catalyst layer obtained in Examples 1 to 6 and Comparative Examples 1 to 6 was transferred to the surface of the perfluorosulfonic acid-based sub-membrane by a transfer method, and the PTFE substrate was removed to obtain a membrane electrode, which was then assembled with a gas diffusion layer for testing.
[0097] The obtained membrane electrode was subjected to voltage cycling (1.45 V (3 min) / 2.0 V (3 min)) for 10,000 cycles, and the current density was 2 A / cm 2 The corresponding voltage,test results are shown in Table 1.
[0098] According to Table 1, although Comparative Examples 1 and 3 have low contact resistances comparable to those of the embodiments of the present application, their voltage loss values are much higher than those of the embodiments of the present application. While the voltage loss values of Comparative Examples 2 and Comparative Examples 4 to 6 are relatively small, their contact resistance values are relatively high. Therefore, compared with Comparative Examples 1 to 6, the membrane electrode prepared using the anode composite catalyst layer of Embodiments 1 to 6 can have both low contact resistance and excellent stability.
[0099] Table 1 Contact resistance and stability test results
[0100]
[0101] Membrane electrode performance test
[0102] The membrane electrode prepared above was tested using an electrolytic water test bench. The specific test method is as follows:
[0103] 1) Prepare the test environment (water resistivity is greater than 3MΩ / cm), ensure that the water and gas pipelines are correctly constructed, and that the temperature control system can work normally;
[0104] 2) Assemble the electrolytic water fixture. Place the electrolytic water fixture on the table and assemble from bottom to top: cathode end plate → cathode gold-plated plate → graphite plate → cathode gasket → carbon paper → membrane electrode → anode gasket → sintered titanium plate → anode flow channel plate → anode end plate. After all parts are placed, tighten the screws with a torque wrench in a fixed order with a torque of 2 → 3 → 4 → 5 Nm per turn. Then install the electrolytic water fixture on the test bench.
[0105] 3) Install the DC power supply load line and SENSE line, turn on the flow meter so that the upper end of the float is close to the 100mL / min scale line. Press the heating button. Wait for the fixture temperature to rise to the set temperature of 80℃ and start the test.
[0106] 4) Enter the test program (increase 0.2A / cm per stage 2 , each stage stays for four minutes) to carry out polarization curve test.
[0107] Table 2 shows the voltage values at different current densities. The results show that when the membrane electrode prepared by the anode composite catalyst layer of Examples 1 to 6 of the present application is applied to water electrolysis, it has a lower voltage value at the same current density compared with Comparative Example 2, Comparative Example 4, and Comparative Example 6. It can be seen that the anode composite catalyst layer prepared by the examples of the present application has a better catalytic effect.
[0108] Table 2 Membrane electrode performance test results
[0109]
[0110] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.
Claims
1. An anode composite catalyst layer, located between the proton exchange membrane and the gas diffusion layer of the membrane electrode, characterized in that: include: an iridium catalyst layer having a first surface and a second surface opposite to each other, wherein the first surface faces the proton exchange membrane and the second surface faces the gas diffusion layer, the iridium catalyst layer comprising a first ionomer and an iridium catalyst dispersed in the first ionomer; The platinum conductive layer has a third surface and a fourth surface opposite to each other, wherein the third surface contacts the second surface of the iridium catalyst layer and the fourth surface faces the gas diffusion layer, and the platinum conductive layer comprises a second ionomer and platinum nanoparticles with a particle size of 10 nm to 500 nm dispersed in the second ionomer.
2. The anode composite catalyst layer according to claim 1, characterized in that: The particle size of the platinum nanoparticles is 90 nm to 120 nm; the thickness of the platinum conductive layer is 0.3 μm to 1.5 μm; and the mass ratio of the platinum nanoparticles to the second ionomer is 1:(0.35 to 0.9).
3. The anode composite catalyst layer according to claim 1, characterized in that: The first ionomer and the second ionomer respectively include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820.
4. The anode composite catalyst layer according to any one of claims 1 to 3, characterized in that: The iridium catalyst is IrO2, IrRuO x1 、IrO2 / TiO2、IrO2 / NbO x1 、IrO2 / Ta2O5、IrO2 / WO x1 or IrO2 / Nb2O 5-x2 At least one of the following, wherein x1 is 1-2, and x2 is 0-3.
5. An anode composite catalyst layer slurry, characterized in that: include: An iridium catalyst layer slurry, the iridium catalyst layer slurry comprising: an iridium catalyst, a first ionomer and a first solvent; The platinum conductive layer slurry comprises platinum nanoparticles with a particle size of 10 nm to 500 nm, a second ionomer and a second solvent.
6. The anode composite catalyst layer slurry according to claim 5, characterized in that: The mass ratio of the iridium catalyst, the first ionomer and the first solvent is 1:(0.1-0.5):(5-50); the mass ratio of the platinum nanoparticles, the second ionomer and the second solvent is 1:(0.35-0.9):(10-50).
7. The anode composite catalyst layer slurry according to claim 5 or 6, characterized in that: The first ionomer and the second ionomer respectively include one or more of Nafion D2020, Nafion NR50, Aquivion D79-25B, and HCD-1820; the iridium catalyst is IrO2, IrRuO x 、IrO2 / TiO2、IrO2 / NbO x 、IrO2 / Ta2O5、IrO2 / WO x or IrO2 / Nb2O 5-x At least one of; the first solvent and the second solvent are the same or different and are selected from at least one of isopropanol, ethylene glycol, ethanol, n-propanol and water.
8. A method for preparing an anode composite catalyst layer, characterized in that: The anode composite catalyst layer slurry is prepared using the anode composite catalyst layer slurry described in any one of claims 5 to 7.
9. The method for preparing the anode composite catalyst layer according to claim 8, characterized in that: The preparation method comprises: Using iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of the proton exchange membrane of the membrane electrode by a coating method or a transfer method; Using a platinum conductive layer slurry and forming a platinum conductive layer on the surface of the iridium catalyst layer by a coating method or a transfer method; Alternatively, the preparation method comprises: Using platinum conductive layer slurry and forming a platinum conductive layer on a transfer material by coating or transfer; Using iridium catalyst layer slurry and forming an iridium catalyst layer on the surface of the platinum conductive layer by a coating method; The stacked structure of the platinum conductive layer and the iridium catalyst layer is transferred to the surface of the proton exchange membrane by a transfer method, and the transfer material is removed.
10. A membrane electrode, characterized in that: The invention comprises a proton exchange membrane, a gas diffusion layer and the anode composite catalyst layer according to any one of claims 1 to 4.
Citation Information
Patent Citations
Iridium oxide-platinum composite nano-catalyst as well as preparation method and application thereof
CN113430555A
Anode catalyst layer of water electrolysis hydrogen production membrane electrode, membrane electrode and application
CN116463673A
Water electrolysis double-layer anode with ultralow precious metal loading capacity
CN116949482A
Membrane electrode assembly for PEM water electrolysis capable of improving the electrical conductivity of the electrode layer and method of manufacturing thereof
US20230203679A1
Cited By
Proton exchange membrane electrolyzed water membrane electrode with catalyst layer constructed by mixed ionomers and preparation method of proton exchange membrane electrolyzed water membrane electrode
CN120006312A
Membrane-electrode assembly and water electrolysis cell
WO2026201796A1
